Stakeholders' perspectives on communicating biosecurity to encourage behavior change in farmers - Moya, Sebastian; Lamont, Kate; Brennan, Marnie L.; Ciavarino, Giovanna; Costa, Maria; Allepuz, Alberto; Tamminen, Lena-Mari; Correia-Gomes, Carla; De Carvalho Ferreira, Helena; Dogusan, Mehmet Murat; Imperial, Teresa; De Meneghi, Daniele; et al. (Frontiers in Veterinary Science, 2025)
Effective communication is crucial for strengthening collaboration and ensuring the successful implementation of biosecurity measures against infectious diseases. A collaborative approach, where farmers and veterinarians play a central role in decision-making, may have a greater impact on promoting the implementation of biosecurity practices compared to a top-down approach. The objective of this study was to explore the perspectives of researchers, official services, and industry on the preferred communication methods between farmers and various on-farm stakeholders. Data were collected through four simultaneous focus groups conducted within the framework of the COST Action BETTER project: three involving researchers, and one involving official services and industry people. The data were analyzed using content analysis, which generated three main themes and 13 subthemes: (i) effective methods for communicating biosecurity messages to farmers: direct interaction and practical learning, audio-visual media and support materials, importance of personalization and coordination, and challenges and innovative solutions; (ii) designing an optimal communication system to promote behavioral change in biosecurity: initial strategies for communication: knowledge and trust, integration of technological tools, mandatory programs and coordinated campaigns, continuous training and collaborative learning, and incentives and certifications; and (iii) measuring the success of biosecurity communication programs: evaluation tools and audits, key indicators and benchmarking, measuring attitudes and behavioral changes, and participation and knowledge as additional evaluation metrics. The findings highlight the need for collaborative, personalized, and sustainable approaches to biosecurity communication. This study provides valuable insights to inform the development and implementation of communication programs that remain effective over time.